Pengajaran Agama melalui Pendekatan Multikultural : Strategi dan Peluang - Pratama, Anugrah Amanu; Anshori, Muhammad Maulidan; Mutiara, Elvian; Annisa, Siti Nur (ARZUSIN, 2021)
Indonesia has cultural and even religious diversity. One of the religions that is widely practiced by the Indonesian people is Islam. It is Islamic religious education that relies on the Qur'an and hadith, of course, is a very strong and correct source in solving problems. The teachings of Islam itself certainly have explained a lot about the differences that exist in life. This study uses a qualitative descriptive analysis method. The approach used is aapproach library research or library method. Islamic religious education is a conscious effort that teaches students to better appreciate, believe, fear, and practice the teachings of the Islamic religion which are sourced from the Qur'an & Hadith. According to James Banks, the notion of multicultural education is education for people of color. Basically the strategy in learning management is very connected with the strategy of organizing or combining in the delivery of learning. Religious teaching with a multicultural approach is closely related, even highly recommended to be applied in the world of education in Indonesia.